Identifikasi Faktor Determinan Prevalence of Undernourishment di Kabupaten Tulungagung - Syinta Francisca Margaretha; Fuadiyah Nila Kurniasari; Nurul Muslihah; Annisa Nurul Hakim; Ahmad Ibnu Riza (Institut Nalanda, 2026)
Undernourishment or inadequate food intake is a condition in which a person’s daily food consumption does not meet the minimum energy requirement. Undernourishment has adverse effects on human health. This leads to a decline in productivity and the quality of human resources, which will ultimately result in decreased economic output and increased poverty rates. This study aims to analyze the factors that influence the Prevalence of Undernourishment (PoU) in Tulungagung Regency. This study used a quantitative approach with a cross-sectional research design. The sample consisted of 125 households that met the inclusion criteria. The research instruments used were questionnaires containing respondent identity, sociodemographic characteristics, economic conditions, food access, consumption patterns, food security status, and household dietary intake. The statistical tests used were the Chi-Square Test to determine the relationship between two categorical variables, followed by logistic regression analysis with a 95% confidence interval. The results showed that the per capita protein category variable was the strongest predictor of household energy inadequacy in Tulungagung Regency (AOR = 11.908; p < 0.001). The second significant variable was house type (AOR = 3.587; p = 0.020). The conclusion of this study is that the factors most influencing the Prevalence of Undernourishment (PoU) in Tulungagung Regency are per capita protein intake and house type.